EVOLUTION OF THE PHASES OF QUASICRYSTALLINE ALLOYS ICOSAHEDRAL/ DECAGONAL Al62.2Cu25.3Fe12.5/Al65Ni15Co20 AND OXIDATIVE BEHAVIOR - Agostinho Jamshi, Lourdes Cristina Lucena; Jamshidi Rodbari, Reza (Journal of the Chilean Chemical Society, 2018)
In this paper, we present an approach and investigation on the evolution of the icosahedral and decagonal phases of quasicrystalline alloys Al62.2Cu25.3Fe12.5 E Al65Ni15Co20, the oxidation behavior in them. The quantification of the quasicrystalline and crystalline phases present in the quasicrystals provides important information in the mass transport by diffusion, as well as the phase transformations that occurred. For this purpose, X-ray diffraction (XRD) and Rietveld Method Quantification, Scanning Electron Microscopy (SEM) / Dispersive Energy Spectroscopy (EDS), Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis). The results showed structural aspects of the two compositions of quasicrystals, these were elaborated and obtained in an arc induction furnace. The oxidation of the alloy Al62.2Cu25.3Fe12.5 showed intermetallic phases with associations of the elements of the alloy and above 735 °C was observed that the crystalline phase is stable in the icosahedral phase. The quasicrystals Al65Ni15Co20, with the interaction of oxygen, happens in the surface of symmetry 10 times plane perpendicular vector. The formation of a thin film of the aluminum oxide with a well ordered hexagonal shape structure, with a domain opposite the decagonal phase with lateral size at about 35 Å.